Shifting Identity of Tamu Lhosar From Cultural To Political - Gurung, Lina (Himalayan Journal of Sociology and Anthropology, 2017)
Tamu Lhosar is Gurungs' New Year which is celebrated every year in the 15th of Poush (approximately December 30) is the biggest festival for Gurungs (Tamu). Tamu Lhosar has become a national festival and enjoys public holiday. This paper aims at exploring out the changing practice of Tamu Lhosar celebrated in Kathmandu Valley through ethnographic approach. Interview, interaction, participant’s observation were done to gather information. Besides, relevant literature was reviewed and, speech given in the program, press release and media news were also analyzed. I tried to apply both in emic and etic perspective in this research. The research found that Tamu Lhosar was stated to celebrate in Kathmandu in 2036 BS (1979 A.D) and then every year. It has been celebrating not only for preserving their culture, cultural identity, and uniting all Tamus residing in Kathmandu valley but also for raising awareness, demonstrating strength and advocating for their rights and issues. Along with changing socio-cultural and political context of the country, the practice of Tamu Lhosar is changing. The move is looking towards social and political transformation. In the starting years, it was celebrated with aim to preserve and promote culture, language and cultural identity of the Gurung community. But nowadays, its purpose has become wider and multipurpose. Tamu Lhosar is more focused in cities and urban areas. The inter organizations (Tamu samaj) of Gurung community actively participate in the festivals demonstrating their folk songs, dance, dresses and ritual activities. Now, Gurungs use this festival also as a platform to expose their cultural identity and political power as well. The big mass of the community that gather every year in the open central space of Kathmandu city has drawn the attraction of the people nationwide, activist and major political parties and leaders. The young generation are also boosting up the importance of Tamu Lhosar in the urban context. The celebration of Tamu Lhosar no more carry the message of their cultural preservation but its practice has shifted beyond it and demands for the institutionalization of their rights through their own federal state in the country. The ethnic identity of Gurungs thus now is marching for political identity.Himalayan Journal of Sociology & Anthropology - Vol. VII (2016), Page: 96-110